PENGARUH PRODUCT QUALITY, BRAND IMAGE DAN SALES PROMOTION TERHADAP PURCHASE DECISION (STUDY PADA KONSUMEN TUMBLER TUPPERWARE) - Ramadhan Dinta Pramana (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Tupperware is one of the companies in the home appliance industry that produces tumblers that has won Top Brand awards for 3 consecutive years in Indonesia. Indonesia is Tupperware's most significant target market with the 2nd largest number of buyers globally. This article discusses Tupperware tumbler purchase decisions' brand image, product quality, and sales promotion. The number of consumer purchases measures the success of a company's sales. Data analysis used a multiple linear regression with SPSS 26, and the total respondent were 100 respondents. The measurement scale used the Likert scale. This study indicates that brand image, product quality, and sales promotion have a significant and positive effect on purchasing decisions. This study recommends Tupperware maintain a positive brand image, provide optimal product quality, and carry out more sales promotions to increase sales. This study also shows that good quality Tupperware tumbler products encourage consumers' decision to buy. Brand image increases consumer confidence in buying or using the product. In contrast, sales promotion encourages consumers to buy Tupperware tumblers.